Effect of clinicians training on their knowledge of abortion and postabortion care in six hospitals in Rwanda - Jean Pierre Bucyebucye; Patrick Gatsinzi Bagambe; Diomede Ntasumbumuyange; Gerard Kaberuka; Zubeda Igiraneza; Marie Laetitia Ishimwe Bazakare; Thomas Ugiruwatuma; Alice Igiraneza; Charlotte Ntakirutimana; Samson Habimana (Women's Health)
Background: Complications of unsafe abortion are public health issue and account for 13% of maternal mortalities globally. Maternal mortality in Rwanda remains high at 203/100,000 live births. Prevalence of unintended pregnancy in Rwanda is estimated at 12%, abortion-related complications are estimated at 10.7 per 1000 and abortion-related maternal mortality remains high (8%). Existing literature suggests that many clinicians face challenges in delivering reproductive health services, including abortion and postabortion care. These challenges often caused by a lack of confidence and insufficient training. Objective: This study aimed to assess the effect of training medical doctors on their knowledge of abortion and postabortion care in Rwanda. Design: A quasi-experimental design was used. Methods: We trained clinicians from six hospitals in Rwanda on abortion and postabortion care using updated national guidelines and the WHO Safe Abortion Care Guideline. Clinicians were trained in 3-h-long sessions over 3 months including lecture and self-learning using shared guidelines books during this period. Pretest and posttest were implemented. In total, four training sessions were held. Training was theoretical only. We compared pretest and posttest scores using paired t -test; p value <0.05 was considered statistically significant. Results: Thirty medical doctors from district and referral hospitals were trained. There was an increase in marks between pretest and posttest. This increase was statistically significant among trainees from three district hospitals with p values 0.046, <0.001, and <0.001, respectively. This increase was statistically significant among both gender groups of participants with p value of 0.005 and 0.001 for male and female trainees, respectively. There was no statistically increase in marks for trainees in teaching hospitals ( p value = 0.168). Conclusion: We found a statistical increase in marks comparing pre- and posttest scores for clinicians attending district hospitals. This increase was observed in both male and female trainees. This increase in marks suggests that the training had a positive impact on clinicians’ knowledge that impacted their decision making and elaboration of management plan for abortion and postabortion care provision.